Bears, bears, everywhere - Milios, Rita.; Dunnington, Tom; Hillerich, Robert L., 1927- (Chicago : Childrens Press, 1988)
An observer of one bear in the air, two bears on the stair, counts all the way up to ten bears huffing and puffing and is relieved that they're full of stuffing.
"Level B, early fluent"--Cover p. [4].
Includes word list.
Booklist.
1.5.
1.5
K-3
Keywords: Counting; Stories in rhyme; Teddy bears -- Fiction; Counting; Stories in rhyme; Teddy bears -- Fiction